COMPARATIVE ANALYSIS OF COMPLIANCE WITH MANDATORY SPENDING IN THE EDUCATION AND INFRASTRUCTURE SECTOR IN THE 2025 MEDAN CITY BUDGET - Gilberta Naibaho; Septi Lumbantobing; Naomi Tarigan; Iskandar Muda; Andy Mulia (JIAR : Journal Of International Accounting Research, 2025)
The Regional Revenue and Expenditure Budget (APBD) is a fiscal policy instrument that determines development direction and public resource allocation priorities. This study analyzes the structure of regional expenditure and evaluates budget proportions in the education and infrastructure sectors of the Medan City Budget for the 2025 fiscal year. Using a quantitative descriptive approach with comparative analysis, the research relies on secondary data from APBD documents and budget realization reports. The findings show total regional expenditure of Rp7.07 trillion, with 22.34% allocated to education and 45.19% to infrastructure. Administratively, both sectors meet mandatory spending provisions. However, substantively, budget allocation tends to favor physical development over human capital investment. The education sector remains close to the minimum threshold, indicating a compliance-oriented approach, while infrastructure dominates regional priorities. These results suggest that formal fiscal compliance does not fully reflect balanced development quality. Therefore, reorienting toward performance-based budgeting is essential to enhance public services and community welfare.